Pengaruh Kepemimpinan, Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Pertanian dan Perkebunan Kabupaten Bireuen - Mutia, Laila; Syahriani, Endang; Mirza, Mirza (Aceh Cooperative Care, 2024)
The research aims to test hypotheses about the influence of leadership, competence and work discipline, partially and simultaneously on employee performance. The study was conducted at the Bireuen Regency Agriculture and Plantation Service. Data collection took the form of a survey through a questionnaire that was prepared and tested for validity and reliability. Carried out using an associative descriptive method with a path analysis approach. The research results prove that (1) there is a significant influence of leadership on the performance of Bireuen Regency Agriculture and Plantation Service employees, namely 43.01%. The influence of competence is 47.91% and the influence of work discipline is 43.41%. (2) Simultaneously, leadership, competence and work discipline contribute to increased performance by 46,5%. (3) There is a causal relationship between leadership and employee competency of 34.8%. The relationship between competency and employee work discipline is 48.3% and the relationship between work discipline and leadership is 41.4%.